The effect of augmenting early nutritional energy delivery on quality of life and employment status one year after ICU admission. Issue 3 (May 2016) - Reid, D. B.; Chapple, L. S.; O'Connor, S. N.; Bellomo, R.; Buhr, H.; Chapman, M. J.; Davies, A. R.; Eastwood, G. M.; Ferrie, S.; Lange, K.; McIntyre, J.; Needham, D. M.; et al.
Augmenting energy delivery during the acute phase of critical illness may reduce mortality and improve functional outcomes. The objective of this sub-study was to evaluate the effect of early augmented enteral nutrition (EN) during critical illness, on outcomes one year later. We performed prospective longitudinal evaluation of study participants, initially enrolled in The Augmented versus Routine approach to Giving Energy Trial (TARGET), a feasibility study that randomised critically ill patients to 1.5 kcal/ml (augmented) or 1.0 kcal/ml (routine) EN administered at the same rate for up to ten days, who were alive at one year. One year after randomisation Short Form-36 version 2 (SF-36v2) and EuroQol-5D-5L quality of life surveys, and employment status were assessed via telephone survey. At one year there were 71 survivors (1.5 kcal/ml 38 versus 1.0 kcal/ml 33; P =0.55). Thirty-nine (55%) patients consented to this follow-up study and completed the surveys (n = 23 and 16, respectively). The SF-36v2 physical and mental component summary scores were below normal population means but were similar in 1.5 kcal/ml and 1.0 kcal/ml groups ( P =0.90 and P =0.71). EuroQol-5D-5L data were also comparable between groups ( P =0.70). However, at one-year follow-up, more patients who received 1.5 kcal/ml were employed (7 versus 2; P =0.022). The delivery of 1.5 kcal/ml for a maximum of ten days did not affect self-rated quality of life one year later.